Good Corporate Governance dan Ukuran Perusahaan Pengaruhnya Pada Tax Avoidance - Tandean, Vivi Adeyani (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 1 (2016), 2016)
This study aims to examine empirically the effect of the application of GCG and the size of the company on tax avoidance. This study was performed on companies listed on the Stock Exchange 2010-2013. Variables used are institutional ownership, the independence of auditors, the audit committee, and the size of the company as an independent variable and tax avoidance as the dependent variable. The research sample 84 manufacturing companies. The sampling technique using judgment sampling. Testing data using multiple regression analysis. The test results showed that only affects the audit committee on tax avoidance. Keywords: Corporate governance, size, tax avoidance
Keywords: corporate governance, size, tax avoidance